Electrical transport across nanometric SrTiO3 and BaTiO3 barriers in conducting/insulator/conducting junctions - Navarro Fernández, Henry Luciano; Sirena, Martin; Gonzalez Sutter, Jesus Ignacio; Troiani, Horacio Esteban; del Corro, Pablo Guillermo; Granell, Pablo Nicolás; Golmar, Federico; Haberkorn, Nestor Fabian (Institute of Physics Publishing, 2018)
Fil: Navarro Fernández, Henry Luciano. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina